(untitled) (International journal of artificial intelligence, 2026)
Attracting investments in green technologies is a critical prerequisite for achieving sustainable development and mitigating environmental degradation. International experience demonstrates that green investments, particularly foreign direct investment (FDI), play a decisive role in promoting environmentally friendly technologies, enhancing resource efficiency, and accelerating technological innovation. This article examines foreign practices of attracting investments in green technologies, with a focus on inward and outward FDI, green finance instruments, environmental regulation, and institutional factors. Using a qualitative analytical approach based on international empirical studies, the paper systematizes the mechanisms through which green investments influence sustainable development. The findings indicate that green FDI, technology transfer, managerial foreign experience, and supportive regulatory environments significantly stimulate green innovation and environmental performance. The study contributes to the growing literature on green finance by identifying policy-relevant lessons for countries aiming to strengthen their green investment frameworks.